Multimodal management of dental pain with focus on alternative medicine: A novel herbal dental gel - A Kumarswamy (Wolters Kluwer Medknow Publications, 2016)
Dental pain is the most common symptom associated with a wide array of dental problems and significantly impacts the oral health-related quality of life. The epidemiology and prevalence of oral diseases that could lead to dental pain are diverse and indicate regional variations. Several researchers have dwelled into the neurobiology and pathophysiology of dental pain making the pain pathways more clear and deciphering the precise targets for the management of pain. Although a number of pharmacological drugs are available in the market, a significant percentage of the population in India prefers alternative herbal medication for relief from dental pain due to the side effects and interactions of pharmacological treatment. However, there is a void in dental literature pertaining to the use, benefits, and safety of the herbal medicines. Therefore, the present assessment has been penned down, focusing on the current multimodal approaches for treating dental pain, the current unmet need, and the role of herbal medication in India for the management of dental pain, with a discussion on novel herbal dental gel.